Pengembangan usaha kimbab sebagai media pembelajaran kewirausahaan di kalangan mahasiswa - Aisyah, Azwa Putri (Maliki Interdisciplinary Journal, 2025)
The growing popularity of Korean culture in Indonesia, especially among young people, has opened up new opportunities in the world of entrepreneurship. One of the tangible forms of this opportunity is the kimbab business, a Korean specialty food that is now increasingly favored by the Indonesian people. This study aims to analyze the potential of kimbab business development as a medium for entrepreneurship learning among students. The methods used in this research are literature study and field observation of consumer interest and student practice in running kimbab business. The results showed that kimbab business can be an effective means to develop students’ entrepreneurial spirit, train managerial skills, and increase creativity and product innovation. In addition, the Korean Wave trend is a significant supporting factor in marketing this product. Therefore, the development of kimbab business not only provides financial benefits, but also educational value for students who are directly involved in the business process. Keywords : kimbab; student entrepreneurship; Korean Wave; culinary business; practical learning